Clinicopathological and Prognostic Features of Ovarian Tumors – An Institutional Look - Akbar, Aisha; Khalid, Ahmareen; Kumar, Ashok (International Journal of Pathology, 2018)
Ovarian cancer is one of the most common malignancies in Pakistan. Due to high incidence andmortality rate, it is important to determine changing trends in ovarian tumors in different settings.Knowing histological subtypes, grading and staging of tumor also has prognostic significance. The present studywas carried out to determine histopathology and clinico-pathologic features of malignant ovarian tumors.Methods: It is retrospective study of 80 cases of malignant ovarian masses in 3 years, received in HistopathologyDepartment of Pakistan Institute of Medical Sciences, Islamabad. Histological typing and grading of the tumorwas done according to WHO criteria. Undifferentiated tumors were identified using immunohistochemistrypanel. Different clinico-pathological parameters were assessed including age of the patient, peritoneal fluidinvolvement ovarian surface involvement, omental metastasis, nodal involvement, and invasion of other adjacentorgans.Results: 80 cases of malignant ovarian neoplasms were included. 51(63.7%) patients presented in age group 20-40 years. Majority of the patients 45 (52%) presented with high tumor grade (poorly differentiated andundifferentiated tumors). Most frequent tumors were surface epithelial tumors comprising 53 (66.2%) of all cases.Serous cystadenocarcinoma was most common among epithelial tumors. Dysgerminoma was most common ingerm cell tumors comprising 21(26.2%) cases. Positive peritoneal fluid cytology for malignant cells was seen intotal 37(46.25) cases, most commonly in dysgerminoma. 17 (53.1%) cases of serous adenocarcinoma and 3 (50%)cases of endometrioid carcinoma showed capsular invasion.Conclusion: Higher frequency of ovarian tumors was seen in reproductive age group. Epithelial tumors weremost common in our setup, most frequent being serous cystadenocarcinoma. Peritoneal fluid cytology waspositive in majority of the patients being an important independent prognostic marker. Serous and endometrioidcarcinoma showed association with poor prognostic factors like capsular invasion and omental metastasis.